Pengaruh Inovasi Produk dan Promosi melalui Strategi Konten Kreatif di Media Sosial terhadap Kinerja UMKM yang bersertifikasi Halal di kabupaten Bone - Hikmah, Nur; Mutalib, Ahmad Abdul; Marzuki, Sitti Nikmah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of product innovation and promotion through creative content strategies on social media on the performance of halal-certified Micro, Small, and Medium Enterprises (MSMEs) in Bone Regency. Product innovation and promotion are strategic factors that can enhance the competitiveness of MSMEs, particularly in the digital era where social media has become the primary marketing channel. The research employed a quantitative approach with an associative method and the Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis technique. Primary data were collected through questionnaires distributed to 140 respondents using a purposive sampling technique. The research instrument utilized a 5-point Likert scale, which had passed validity and reliability testing. The results indicate that product innovation has no significant effect on creative content strategies on social media (t=0.453, p = 0.651) and MSME performance (t=0.265, p= 0.791). Conversely, promotion significantly affects creative content strategies on social media (t = 8.727, p0.000) and MSME performance (t = 2.106, p = 0.036). Creative content strategies on social media have a significant effect on MSME performance (t = 7.261, p = 0.000). Furthermore, creative content strategies significantly mediate the relationship between promotion and MSME performance (t = 5.197, p = 0.000), but do not mediate the relationship between product innovation and MSME performance (t = 0.449, p = 0.653). The implications of these findings suggest that promotion packaged through creative content strategies on social media plays an important role in enhancing the performance of halal-certified MSMEs. Meanwhile, product innovation needs to be supported by relevant marketing strategies to contribute effectively to performance. Therefore, business actors, the government, and other stakeholders should focus on improving digital marketing skills to maximize the potential of social media promotion.